Urban Dreams : Transformations of Family Life in Burkina Faso. - Roth, Claudia, 1955-2012 (Berghahn Books, Incorporated, 2018)
Claudia Roth's work on Bobo-Dioulasso, a city of half a million residents in Burkina Faso, provides uniquely detailed insight into the evolving life-world of a West African urban population in one of the poorest countries in the world. Closely documenting the livelihood strategies of members of various neighbourhoods, Roth's work calls into question established notions of "the African family" as a solidary network, documents changing marriage and kinship relations under the impact of a persistent economic crisis, and explores the increasingly precarious social status of young women and men.